Etika Politik Dan Kualifikasi Calon Legislatif Dalam Pemilu: Perspektif Fiqih Siyasah - Askana Fikriana; M. Kahfi Rezki (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
General Election (Pemilu) in Indonesia is a special process involving the entire society in determining the leadership of the state. However, the qualifications of a leader often differ from the desired ideals. This research explores the political structure and ethics of Islam in the context of contemporary politics. The principles of Islamic politics encompass unity through consultation, trustworthiness, upholding fair law, and obedience to Allah, the Prophet, and those in authority. From the perspective of siyasah fiqh, the regulation of human interests, including the state, is governed by Islamic teachings. Ethics play a crucial role in guiding political behavior, ensuring actions that are right and just for the common good. As a significant belief, Islamic leadership demands integrity, deep knowledge of religion, and the ability to apply Islamic teachings in everyday life. Moreover, integrity, honesty, and wisdom in leadership are key attributes desired in an Islamic leader. Effective communication and good relations with the community are also important in choosing the right leader. By considering these criteria, we can ensure that Islamic principles are reflected in public policies. This research provides a foundation for selecting an ideal leader in the legislative domain in the future, ensuring that leadership reflects the desired Islamic values of the community.